Medical biometrics first international conference, ICMB 2008, Hong Kong, China, January 4-5, 2008 : proceedings - ICMB 2008 (Lecture notes in computer science, 2007)
The past decade has seen a rapid growth in the demand for the usage of behavioral and physiological characteristics of humans for e-security and forensics applications. The significant advances in the biometrics techniques are increasingly incorporated in a number of other applications. In this context, medicine has emerged as the largest and most promising area. Medical biometrics primarily refers to the usage of beh- ioral and physiological characteristics of humans for medical diagnosis and body care. Thus the goal of medical biometrics is to explore solutions to the open problems in medicine using biometric measurements, technologies and systems. The International Conference on Medical Biometrics (ICMB 2008) was the first major gathering in the world devoted to facilitating this interaction. We are pleased that this conference attracted a large number of high-quality research papers that will benefit international medical biometrics research. After a careful review process, 40 papers were accepted either for oral (17) or poster (23) presentations. In addition to these technical presentations, this conference also held a workshop on Computerized Traditional C- nese Medicine. Our efforts are focused to generating awareness among researchers, organizing researchers to foster research in this area, and providing a common platform for discussion and investigation. This conference provided a forum for discussing prac- cal experiences in applying the state-of-the-art biometric tecnologies for medical diag- sis and body care, which will further stimulate research in medical biometrics. We are grateful to Max A.